The use of social media for professional purposes by healthcare professionals: the #intEHRAct survey. Issue 4 (9th October 2021) - Guerra, Federico; Linz, Dominik; Garcia, Rodrigue; Kommata, Varvara; Kosiuk, Jedrzej; Chun, Julian; Boveda, Serge; Duncker, David
Abstract: Social media (SoMe) represents a medium of communication in everyday life and has gained importance for professional use among clinicians. In the #intEHRAct survey, we aimed to describe the use of SoMe by the healthcare community in a professional setting. The EHRA e-Communication Committee and the Scientific Initiatives Committee prepared a questionnaire and distributed it via newsletters, Twitter, LinkedIn, and Facebook. The survey consisted of 19 questions made on an individual basis and collected anonymously. Two hundred and eighty-five responders from 35 countries (72.3% male, age 49 ± 11 years old) completed the survey. Most respondents (42.7%) declared to use SoMe as passive users while 38.3% and 19.0% declared to share content on a non-daily and daily basis, respectively. The respondents estimated they spent a median of 5 (Q1–Q3: 2–10) h per week on SoMe. The most widely used SoMe was LinkedIn (60.8%), but the use of each platform was heterogeneous between countries. Among the advantages of SoMe, respondents indicated the chance of being updated on recent publications (66.0%), networking (48.5%), and the availability of rare or interesting cases (47.9%) as the most useful. Regarding the disadvantages of SoMe, the respondents underlined the loss of personal contact (40.7%), the inability to get 'hands-on' training (38.7%), and the lack of control regarding quality of scientific evidence (37.1%). Social media is increasingly used for professional purposes for scientific updating, networking, and case-based learning. The results of this survey encourage scientific societies, journals, and authors to enhance the quality, reach and impact of scientific content provided through SoMe.